A First Case Report of DiGeorge Syndrome from Ethiopia Highlights Challenges in Identifying and Treating Children with Primary T-Cell Deficiencies in Low Resource Settings - Tinsae Alemayehu; Solomie Jebessa Deribessa (Case Reports in Immunology)
Background. Cellular primary immunodeficiencies are rarely reported from Africa. DiGeorge syndrome is a commonly recognized form of a congenital T-cell deficiency. The disorder is characterized by hypoplastic or aplastic thymus, hypocalcemia, recurrent infections, and other associated congenital defects. Case Report. We report an eleven-month-old infant presenting with recurrent chest and diarrheal infections, failure to thrive, lymphopenia, hypocalcemia, and hypoplastic thymus on imaging. A diagnosis of DiGeorge syndrome was confirmed after determining very low CD3 and CD4 levels. Conclusions. We describe the first case report of an Ethiopian child with a congenital T-cell immunodeficiency. We have outlined essentials for diagnosis and management of cellular primary immunodeficiency disorders in low resource settings.